Incorporation of Nanoparticles Based on Zingiber Officinale Essential Oil into Alginate Films for Sustained Release - Rosli, Nur Ayshah (2022)
This research focused on the formulation of Ca2+ cross-linked alginate (Alg) gels containing Zingiber officinale oil extract (ZOE) loaded into a nanostructured lipid carrier (NLC). The NLC is intended to protect the Zingiber officinale oil against physical and chemical degradation during topical administration to sustain the drug release and reduce drug leakage during storage. The NLC was prepared using hot homogenisation and ultrasonication of glyceryl monostearate. Virgin coconut oil was used as the liquid lipid. The NLC-ZOE had a mean size diameter of 100 nm and a zeta potential value of −40 mV. The ZOE released from NLC followed the Korsmeyer-Peppas model case I (Fickian diffusion). The NLC-ZOE formulation was then incorporated into Alg. The gels were prepared via ionotropic gelation in the presence of calcium. Scanning electron microscopy (SEM) images of Alg films revealed successful intercalation of NLC within the Alg matrix. The in vitro ZOE release from NLC-ZOEAlg occurred in a sustained manner from the cross-linked Alg hydrogels compared to the free NLC. The profiles of NLC-ZOE released from the Alg films depended on the nanoparticles amount. The results demonstrated the importance of designing a local delivery system to entrap and control the release of the bioactive components of ZOE from within the Alg matrix. Ca2+ cross-linked Alg gels containing ZOE loaded into NLC was found to be suitable for topical delivery applications, as shown by the sustained release of ZOE from calcium cross-linked Alg films containing NLC that was demonstrated in this study.